2008
DOI: 10.1016/j.mib.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella-containing vacuole—Moving with the times

Abstract: SummarySalmonella pathogenesis is dependent on its ability to invade and replicate within host cells. Following invasion the bacteria remain within a modified phagosome known as the Salmonellacontaining vacuole (SCV), within which they will survive and replicate. Invasion and SCV biogenesis are dependent on two Type III Secretion Systems, T3SS1 & T3SS2, which are used to translocate distinct cohorts of bacterial effector proteins into the host cell. Elucidating the roles of individual effector proteins in SCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
277
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(295 citation statements)
references
References 79 publications
5
277
0
Order By: Relevance
“…For comparison, we also monitored distribution of another LGP, LAMP1 (lysosomal-associated membrane protein 1) in infected HeLa epithelial cells. In agreement with previous studies, 34,36 the infected epithelial cell showed long SIF connected to LAMP1-positive SCV (Fig. 1A).…”
Section: S Typhimurium Induces In Fibroblasts Aggregates Enriched Insupporting
confidence: 93%
See 1 more Smart Citation
“…For comparison, we also monitored distribution of another LGP, LAMP1 (lysosomal-associated membrane protein 1) in infected HeLa epithelial cells. In agreement with previous studies, 34,36 the infected epithelial cell showed long SIF connected to LAMP1-positive SCV (Fig. 1A).…”
Section: S Typhimurium Induces In Fibroblasts Aggregates Enriched Insupporting
confidence: 93%
“…16,17 We hypothesized that a distinct SCV biogenesis could be responsible for this nonproliferative state. As SCV accumulate lysosomal membrane glycoproteins (LGP) in epithelial cells, 22,34,36 we examined the distribution of SCARB2/Limp-II, a lysosomal integral membrane protein in S. Typhimurium-infected NRK-49F fibroblasts, fixed and processed for immunofluorescence microscopy. For comparison, we also monitored distribution of another LGP, LAMP1 (lysosomal-associated membrane protein 1) in infected HeLa epithelial cells.…”
Section: S Typhimurium Induces In Fibroblasts Aggregates Enriched Inmentioning
confidence: 99%
“…Previous studies have shown that intracellular pathogens either mimic or target these proteins to establish their niche in the host cells (20,21,24). Similarly, maturation of SCP also depends on the sequential removal and recruitment of different Rabs and syntaxins (2,3,15,19,28). In this study, we have determined the recruitment of different syntaxins on SCP at various stages of their maturation in macrophages and have shown that SCP specifically recruit higher amounts of Syntaxin6 after 90 min of internalization than at 5 min of internalization.…”
Section: Discussionmentioning
confidence: 81%
“…typhimurium is an intracellular Gram-negative pathogenic agent that survives in a special vacuole called the Salmonellacontaining vacuole (SCV) after internalization into the macrophages or epithelial cells. 109 Two different T3SSs, T3SS1 and T3SS2, encoded by pathogenicity island-1 (SPI-1) and SPI-2, respectively, are employed by Sa. typhimurium to secrete effector proteins.…”
Section: Shigella Flexnerimentioning
confidence: 99%